The TurkStream Pipeline in Light of the Security of Demand for Russian Gas - Virag, Attila (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to analyse the TurkStream project in light of the security of demand for Russian natural gas. The analysis focuses on the relations between the EU and Russia, with further focus on Eastern Europe, accompanied by a description of the power engineering actions affecting the old continent from 2014 to date. Based on the analysis, it can be established that although on the face of it, the Russian-inspired project has policy and business goals, but demand security considerations also lie in the background, fuelled by significant geopolitical endeavours.